2011
DOI: 10.1093/jee/104.4.1212
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Fumigant Toxicity of Some Essential Oils Against Ephestia kuehniella

Abstract: The chemical constituents of some essential oils extracted from aromatic plants (savory, Satureja thymbra L.; Turkish oregano, Origanum onites L.; myrtle, Myrtus communis L.; marjoram, Origanum majorana L.; laurel, Laurus nobilis L.; lemon, Citrus limon L.; sticky goosefoot, Chenopodium botrys L.; and tansy, Tanecetum armenum [DC.] Suchultz Bip.) were analyzed by gas chromatography-mass spectrometry. Fumigant toxicity of volatile compounds was tested against Mediterranean flour moth, Ephestia kuehniella (Zelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The present results indicated that fumigant toxicity varied with insect species, oil concentration and exposure time (Choi et al 2003;Sedy and Koschier 2003;Negahban et al 2007;Ayvaz et al 2009Ayvaz et al , 2010Karabörklü et al 2010Karabörklü et al , 2011. LC50 and LC95 of the EO were 39 and 49 mL/L air at 96 h for A. obtectus.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The present results indicated that fumigant toxicity varied with insect species, oil concentration and exposure time (Choi et al 2003;Sedy and Koschier 2003;Negahban et al 2007;Ayvaz et al 2009Ayvaz et al , 2010Karabörklü et al 2010Karabörklü et al , 2011. LC50 and LC95 of the EO were 39 and 49 mL/L air at 96 h for A. obtectus.…”
Section: Discussionmentioning
confidence: 54%
“…Ten emerging adult insects were collected and placed into glass jars. EO was applied on a blotting paper strip (3 ¥ 3 cm), which was attached to the underside of the jars lid (Karabörklü et al 2011). Insects were exposed to EO at the doses of 20-160 mL/L for 24-96 h. Dead adults were counted, and the percentage of mortality was determined for each application dose and exposure period.…”
Section: Test Insects and Toxicity Bioassaysmentioning
confidence: 99%
“…Previous studies describing the biological properties of Citrus oils highlight their potential for the control of different arthropods. Regarding the species investigated in the present study, the literature offers reports on the effect of the EO from Citrus limon against pests of interest to veterinary medicine (Aboelhadid, Mahrous, Hashem, Abdel‐Kafy, & Miller, ), human medicine (Selvakumar, Gokulakrishnan, Elanchezhiyan, & Deepa, ), agriculture (Martins, Zago, Costa, Araujo Junior, & Carvalho, ) and grain storage (Karabörklü, Ayvaz, Yilmaz, & Akbulut, ). The EO from Citrus reticulata is also reported to have action against pests of interest to human medicine (Badawy et al, ), agricultural activities and grain storage (Badawy et al, ; Mishra, Tripathi, & Tripathi, ), including the two‐spotted spider mite (Choi, Lee, Park, & Ahn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies describing the biological properties of Citrus oils highlight their potential for the control of different arthropods. Regarding the species investigated in the present study, the literature offers reports on the effect of the EO from Citrus limon against pests of interest to veterinary medicine (Aboelhadid, Mahrous, Hashem, Abdel-Kafy, & Miller, 2016), human medicine (Selvakumar, Gokulakrishnan, Elanchezhiyan, & Deepa, 2015), agriculture (Martins, Zago, Costa, Araujo Junior, & Carvalho, 2017) and grain storage (Karabörklü, Ayvaz, Yilmaz, & Akbulut, 2011). The EO from…”
Section: Fumigant and Residual Contact Bioassaymentioning
confidence: 99%
“…This plant is known as sweet Marjoram in some countries. Several health benefits of that plant are its disinfection role, anti‐diabetes, carminative, antispasmodic, stimulant, diaphoretic and diuretic, anti‐asthma, to treat coughs, indigestion, rheumatism, headaches, and toothache (Karabörklü, Ayvaz, Yilmaz, & Akbulut, ; Rau, Wurglics, Dingermann, Abdel‐Tawab, & Schubert‐Zsilavecz, ; Sagdic, Ozturk, Bayram, Kesmen, & Yilmaz, ). Main Marjoram content includes moisture (8%), protein (14%), oil (5.6%), fiber (22%), ash (6–24%), and oil essential (1.8%).…”
Section: Introductionmentioning
confidence: 99%